Mixed histiocytosis: a case report - Ullauri-Zambrano , Verónica (2022)
Introduction: Histiocytoses are rare diseases characterized by tissue infiltration by abnormal histiocytes. They are divided into five groups. They are frequent in the pediatric population. The combination of Langerhans cell histiocytosis and non-Langerhans cell histiocytosis is fortuitous. Case report: We report the case of a 66-year-old female patient who debuted with a history of systemic involvement, in which the presence of tumor masses on the anterior aspect of the legs, generalized bone pain and endocrinological alterations attracted our attention. The diagnosis of mixed histiocytosis was suggested. Treatment with anti BRAF V600E monoclonal antibodies, interferon alpha and/or chemotherapy was recommended. Conclusion: It is possible to make the diagnosis of histiocytosis based on the patient's personal pathological history and the clinical findings with the support of radiological, histological and immunohistochemical studies. Finally, this is the first case of mixed histiocytosis published in Ecuador.